The Under Age Marriage Phenomenon (Case Research in People of Cempaka Banjarbaru South Kalimantan) - Joko Tri Haryanto (Balai Penelitian dan Pengembangan Agama Semarang, 2012)
Marriage becames a milestone for man to build a family life as husband and wife. To construct an idealized family, the Law number 1 in 1974 set a minimum age limit19 years for becoming husband and 16 years for becoming wife. But in practice there are many people who get married under the age limit. This qualitative study revealed the phenomenon of underage married in Cempaka community Banjarbaru District of South Kalimantan.Some factors that drive them to get married are determinist on religious understanding, the abundance of the natural wealth, lack of awareness of education, tolerance of deviation rules, development of social media technology, and the familiarity of the pattern of Cempaka. Motives that drive parents to marry their children off under the age of, among others, is to maintain that children do deviate their association from religious teaching, to hide their shame if their daughter was already pregnant before marriage, and economic motives to help to enlighten the burden on families.